2022
DOI: 10.3390/s22218261
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Synchrotron THz Radiation on the Corneal Hydration Using Synchrotron THz-Far Infrared Beamline

Abstract: Due to increasing interest in imaging, industrial, and the development of wireless communication operating at THz frequencies, it is crucial to ascertain possible health impacts arising from exposure to THz radiation. This paper reports on the pilot study of transmittance and absorbance spectra of the porcine cornea following THz frequency irradiation at a synchrotron THz/Far-IR beamline. The exposure period was 4 hours. One cornea was exposed to the radiation, with a second cornea acting as a control.An Atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The major substance in living systems is liquid water, averaging about 75% [ 21 ]; while water is an essential component of biological tissues, it is relatively simple compared to the complexity of living tissues. Saline solution is often used as a surrogate in labs and medical settings, closely matching the conductivity of many biological tissues.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major substance in living systems is liquid water, averaging about 75% [ 21 ]; while water is an essential component of biological tissues, it is relatively simple compared to the complexity of living tissues. Saline solution is often used as a surrogate in labs and medical settings, closely matching the conductivity of many biological tissues.…”
Section: Methodsmentioning
confidence: 99%
“…These studies find it challenging to conduct real-time assessments of RF propagation on live tissues. In addition, it was observed that the radiation emitted by the Australian Synchrotron is low to induce any detrimental health effects on tissues with a high water content, such as the cornea [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The power attenuation from 0.13 to 0.33 THz has low loss in the atmosphere; hence, this frequency bandwidth will be a reasonable choice for applications such as communications, sensing, and imaging [5]. With the increasing use of mmW and THz radiation in communication and medical applications, the potential impacts of mmW and THz technologies on biological systems become critical [6]. As 5G technology continues to advance and the possibility of 6G operating systems emerges, there is an increasing interest in utilizing higher frequencies of up to 4 THz on the EM spectrum [3].…”
Section: Introductionmentioning
confidence: 99%
“…The human cornea contains 75-80% water. Two natural states of water in biological tissues are known as free "bulk" water (i.e., freely moving water molecules) and bound water [6,20]. Bound water has a lower absorption coefficient than bulk water at THz, which needs to be considered when calculating penetration depth [21].…”
Section: Introductionmentioning
confidence: 99%